The Effects of Lead Exposure on Serum Uric Acid and Hyperuricemia in Young Adult Workers: A Cross-sectional Controlled Study - Ali Erdem BAKİ and Timur EKİZ and Gökhan Tuna ÖZTÜRK and Engin TUTKUN and Hınç YILMAZ and Mustafa Turgut YILDIZGÖREN (Archives of Rheumatology, 2016)
Objectives: This study aims to evaluate the relationship between serum uric acid levels and renal functions in asymptomatic subjects who had occupational lead exposure, particularly for shorter durations whereby saturnine gout has also been discussed. Patients and methods: In this retrospective study, files of 100 males (mean age 34.5±5.9 years; range, 21 to 47 years) with occupational risk for lead exposure and 100 healthy male controls (mean age 34.47±5.8 years; range 21 to 47 years) were reviewed. Demographic characteristics of the subjects and laboratory test results were recorded from the files. Creatinine clearance and 24-hour urinary creatinine were measured in the lead-exposed group. Results: In the lead-exposed group, mean serum uric acid level was higher than those of the control group (p<0.001). Lead exposure time was negatively correlated with 24-hour urinary creatinine levels (r= -0.373, p<0.001). In addition, serum uric acid levels were positively correlated with serum creatinine levels (r=0.412, p<0.001) in the exposed group. Six patients had hyperuricemia (serum uric acid level >6.8 mg/dL) in the lead- exposed group; however, all subjects’ serum uric acid level was lower than 6.8 mg/dL in the control group (p=0.029). Although 22 subjects had higher uric acid levels than 6.0 mg/dL in the lead-exposed group, only one control had higher uric acid level than 6.0 mg/dL (p<0.001). Conclusion: In light of our results, we may conclude that workers with lead exposure have higher frequency of hyperuricemia and higher serum uric acid levels than those of the control group. Therefore, we may imply that higher serum uric acid levels may be associated with renal impairment in lead-exposed subjects even in the earlier stages of exposure.